Polystyrene controlled growth of zerovalent nanoiron/magnetite on a sponge-like carbon matrix towards effective Cr(vi) removal from polluted water. Issue 111 (18th November 2016) - Gu, Hongbo; Lou, Han; Ling, Dong; Xiang, Bo; Guo, Zhanhu
Abstract : Epoxide functionalized polystyrene controlled growth of zerovalent nanoiron/magnetite on a sponge-like carbon matrix (nZVI/Fe3 O4 @C) nanocomposites show a unique Cr(vi ) removal performance over a wide pH range. Abstract : In situ grown zerovalent nanoiron/magnetite on sponge-like carbon matrix (nZVI/Fe3 O4 @C) has been evaluated for the removal of toxic hexavalent chromium (Cr(vi )) from polluted water. This material is synthesized by calcination of the epoxide group-functionalized polystyrene (FPS) as the carbon source under a mixture of 5% hydrogen/argon (v/v) atmosphere. The nZVI/Fe3 O4 @C demonstrates a unique capability to remove Cr(vi ) from polluted water over a wide pH range, and the optimal pH value for Cr(vi ) removal is 5.0 at 298 K. In comparison, only Fe3 O4 @C is formed when the as-received PS is used as the carbon source under the same atmosphere conditions and exhibits a poor Cr(vi ) removal performance (the removal percentage is around 50% relative to nZVI/Fe3 O4 @C). Various factors influencing the Cr(vi ) removal efficiency, such as treatment time, initial Cr(vi ) concentration and nZVI/Fe3 O4 @C dosage, have been systematically studied. The Cr(vi ) removal mechanism is confirmed by X-ray photoelectron spectroscopy (XPS) and Raman tests. The results illustrate that the Cr(vi ) is reduced to Cr(iii ) by nZVI with the simultaneous adsorption of Cr(iii ) via C–O–Fe bonds on nZVI/Fe3 O4 @C. The Cr(vi ) removal kinetics is determined to follow pseudo-first-order behavior with calculated pseudo-first-order rate constants of 0.01582, 0.02555 and 0.03264 min −1 at 298, 308 and 318 K, respectively, at a pH of 5.0. The low value of the activation energy (28.621 kJ mol −1 ) indicates that the Cr(vi ) reduction process on nZVI/Fe3 O4 @C is a fast process. The calculated thermodynamic parameters of this chemical reaction, including negative Δ G 0, positive Δ H 0 and positive Δ S 0, suggest that the Cr(vi ) reduction on nZVI/Fe3 O4 @C is spontaneous and endothermic, and more preferred at higher temperatures. Both the kinetics and thermodynamics show that the nZVI/Fe3 O4 @C is a promising material for highly fast and efficient removal of Cr(vi ) from polluted water.